2002
DOI: 10.2337/diabetes.51.9.2669
|View full text |Cite
|
Sign up to set email alerts
|

The Succinate Mechanism of Insulin Release

Abstract: Nutrient secretagogues can increase the production of succinyl-CoA in rat pancreatic islets. When succinate esters are the secretagogue, succinyl-CoA can be generated via the succinate thiokinase reaction. Other secretagogues can increase production of succinyl-CoA secondary to increasing ␣-ketoglutarate production by glutamate dehydrogenase or mitochondrial aspartate aminotransferase followed by the ␣-ketoglutarate dehydrogenase reaction. Although secretagogues can increase the production of succinyl-CoA, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
47
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 71 publications
(74 reference statements)
4
47
0
2
Order By: Relevance
“…Short Chain Acyl-CoAs-Third, the results support the hypothesis that short chain acyl-CoAs are important for insulin secretion (2,14). In general, acetoacetate and ␣-ketoglutarate were increased by conditions that stimulated insulin release in both islets (Table 6) and INS-1 832/13 cells (Table 8).…”
Section: Tablesupporting
confidence: 67%
See 1 more Smart Citation
“…Short Chain Acyl-CoAs-Third, the results support the hypothesis that short chain acyl-CoAs are important for insulin secretion (2,14). In general, acetoacetate and ␣-ketoglutarate were increased by conditions that stimulated insulin release in both islets (Table 6) and INS-1 832/13 cells (Table 8).…”
Section: Tablesupporting
confidence: 67%
“…In an effort to explain part of the requirement for the high rate of anaplerosis in insulin secretion, we proposed the "succinate mechanism" of insulin release (2,14). This hypothesis used our own data and data from the literature to suggest why methyl esters of succinic acid have consistently been found to be the only insulinotropic esters of any esters of a citric acid cycle intermediate tested, or the most insulinotropic, depending on the individual study.…”
mentioning
confidence: 99%
“…Although INS-1 832/13 cells differ in several aspects of glucose metabolism compared with ␤-cells (7-10), many of the mechanisms that couple insulin secretion to glucose metabolism, such as glucose transport, mitochondrial oxidation, and anaplerosis are similar (1)(2)(3)(4)(5)(6)11). Hence, these results are likely to extrapolate to glucose-stimulated insulin secretion in islets.…”
Section: Methodsmentioning
confidence: 99%
“…Although, it is well established that glucose-stimulated insulin secretion requires mitochondrial carbohydrate oxidation to drive ATP production (1), a number of studies have suggested that intermediates (e.g. malonyl-CoA (2, 3), succinate (4), and glutamate (5)) generated, directly or indirectly, from anaplerosis may act as second messengers linking glucose oxidation with insulin secretion.…”
mentioning
confidence: 99%
“…Furthermore, 10 mmol/l of the monomethyl ester of succinate (methylsuccinate), a secretagogue that may stimulate insulin secretion via flux through the anaplerotic pathway involving malic enzyme or direct activation of complex II (succinate dehydrogenase) in the respiratory chain [20], had no stimulatory effect on insulin secretion in control islets (Fig. 5), confirming previous observations in mouse islets [20]. In contrast, the addition of methylsuccinate to islets from HF mice revealed a dramatic increase in insulin secretion.…”
Section: Stimulation Of Islets In Vitro With Glutamine and Bchmentioning
confidence: 99%